Village Fund Management in Manunggang Julu Village 2017, Southeast Padangsidimpuan Sub-District, Padangsidimpuan, Indonesia - Syulhennisari Siregar (Budapest International Research and Critics University, 2018)
The allocation of village fund is expected to be more optimal in increasing equitable development of village welfare through improving public services in the village, advancing the village economy, overcoming the development gap between villages and strengthening village communities as subjects of development. This paper intends to review and analyze the village fund management in 2017 in Manunggang Julu Village, Padangsidimpuan Sub-district, Southeast Padangsidimpuan. The method used in this writing is a literature review of secondary data collection techniques derived from books, research and journals. This paper concludes that village fund management is carried out on the priority of using funds with the principle of justice, community priority needs and village typology.